Final charged-lepton angular distribution and possible anomalous top-quark couplings in pp→tt¯X→ℓ+X′ - Zenrō Hioki; Kazumasa Ohkuma (Physics Letters B, 2014)
Possible anomalous (or nonstandard) top-quark interactions with the gluon and those with the W boson induced by SU(3)×SU(2)×U(1) gauge-invariant dimension-6 effective operators are studied in pp→tt¯X→ℓ+X′ (ℓ=e or μ) at the Large Hadron Collider (LHC). The final charged-lepton (ℓ+) angular distribution is first computed for nonvanishing nonstandard top-gluon and top-W couplings with a cut on its transverse momentum. The optimal-observable procedure is then applied to this distribution in order to estimate the expected statistical uncertainties in measurements of those couplings that contribute to this process in the leading order.